Fishermen community empowerment strategy through rural fisheries business development Program (Pump) by marine and fisheries office of Padang - Riki Fernando; Asnil Asnil; Erianjoni Erianjoni (Fakultas Ilmu Pendidikan UNP)
This study was based on the low economic condition of small-scale fishermen community in Padang. Ministry of Marine Affairs and Fisheries launched an empowerment of fishermen community through Rural Fisheries Business Development program (PUMP) implemented by the Marine and Fisheries Office of Padang City. The purpose of this research was to see the results of the empowerment strategy toward fishermen community in Padang through Rural Fisheries Business Development Program (PUMP). This research used qualitative by using descriptive method, informant determined by Purposive Sampling. The type of data consisted of primary and secondary data. Data were collected through observation, interview, and documentation study. Data collection tools included interview guides, observation guides, and field notes. Data validity test utilized source triangulation. Data analysis used SWOT analysis through data processing, data analysis, data reduction, and conclusion.